PENGARUH BERKUMUR DENGAN MASERASI EKSTRAK BONGGOL NANAS TERHADAP pH SALIVA RONGGA MULUT - Minarni Minarni (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2019)
Saliva acts as a buffer system to maintain optimum pH of the oral mouth. The Carbohydrate metabolism by oral microorganisms causes demineralization of enamel resulting in dental caries. Maseration of pineapple cobs as solution can increase salivary pH and increase salivary secretion. This study aims to determine the effect of gargling with maceration of various concentrations of pineapple extract to the salivary pH. This research used quasi experiment method with pre-test and post-test without control group design. The sample is 60 students of SDN 10 Kubu. The sample was divided into 4 groups of 15 persons each meeting the inclusion criteria. Group 1 gargled with 25% pineapple hump extract solution, group 2 rinsed with 50% pineapple hump extract solution, group 3 rinsed with 75% pineapple hump extract solution, and group 4 rinsed with aquades. Saliva pH measured using digital pH meter. Data analyzed by Wilcoxon test followed by Kruskal Wallis test. Wilcoxon test showed a significant difference in salivary pH before and after gargling in all groups. From the result of Kruskall-Wallis Test showed significant value 0,01 (p 0,05). There is statistically significant difference between four groups.Conclusion: Gargling with maceration solution of pineapple extracts of various pineapple concentrations can increase the pH of the mouth. The mouthwash contains pineapple extract of 75% has the most influence on the increase of salivary Ph.